2013
DOI: 10.1111/eci.12153
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hormones target nuclear oncogenes c‐Fos and c‐Jun in carcinoma cells

Abstract: Four cardiac hormones are potent inhibitors of c-Fos and c-Jun proto-oncogenes within the nucleus of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, the p-c-Jun protein level increased in the U0126 group. These observations suggested that ERK1/2 might promote the proliferation of Hela and C33A cells through increasing the activation of p-c-Fos protein, while the result of c-Jun protein level increasing after p-ERK1/2 inhibited is opposite to the expectation [17], and the cause should be focused on the further study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the p-c-Jun protein level increased in the U0126 group. These observations suggested that ERK1/2 might promote the proliferation of Hela and C33A cells through increasing the activation of p-c-Fos protein, while the result of c-Jun protein level increasing after p-ERK1/2 inhibited is opposite to the expectation [17], and the cause should be focused on the further study.…”
Section: Discussionmentioning
confidence: 92%
“…Among these proteins, c-Fos and c-Jun are the major subunits of AP-1 which involved in cell proliferation and cell cycle [16] and decreased in carcinoma cells after treated with ERK1/2 inhibitor [17].…”
Section: Introductionmentioning
confidence: 99%
“…It also coordinates with other genes (particularly ERK/MAPK pathway components) to promote cancer cell invasion and migration (Wolfer and Ramaswamy, 2011). And for proto-oncogene c-Fos, it dimerizes with c-Jun to form AP-1 protein to induce transcription of various genes concerning proliferation, differentiation and transformation of cancer (Manimala et al, 2013). All of the three genes play vital roles in carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific cause of the elevation of natriuretic peptide plasma levels seen in cancer has not been elucidated. In recent years, it has been demonstrated that natriuretic peptides, or compounds with similar activity, decrease the number of several cancer cells in vitro through a reduction of DNA synthesis [ 32 ] and inhibition of c-Fos and c-Jun protooncogenes [ 33 ], inhibit lung metastases and skin carcinogenesis in animal models [ 34 , 35 ], and diminish the expression of vascular endothelial growth factor and that of its receptor VEGFR2, thus having the potential to control vasculogenesis [ 36 ]. One work has shown opposite effects of natriuretic peptides on carcinogenesis depending on their concentrations [ 37 ].…”
Section: Discussionmentioning
confidence: 99%